Hubungan Dokumentasi Keperawatan Elektronik Dengan Mutu Handover - Sitah Umu Hakim; Solehudin Solehudin; Lannasari Lannasari (Jurnal Ventilator, 2024)
As technology develops in health, hospitals are using electronic health records. SOAP method nursing documentation is an important element in nursing services, one of the documentation that uses electronics is nursing documentation regarding handover. The aim of this research is to determine the relationship between electronic nursing documentation and handover quality. This type of quantitative research is Analytic Correlation using a cross sectional design. The population in this study was 69 nurses. Sampling used a total sampling technique so that a sample of 69 respondents was obtained. The research instrument is an observation sheet. The statistical test in this study used the Chisquare test. The results of the research obtained an overview of the relationship between the completeness of electronic nursing documentation and the quality of handover. Of the 20.3% of incomplete nursing documentation, 5.8% had good handover quality, and for complete nursing documentation 26.1% had good handover quality of 47.8%. In the chi-square analysis, the significance was p < 0.002. So Ha is accepted, meaning there is a relationship between the completeness of nursing documentation and the quality of electronic-based handover. In conclusion, the results obtained from electronic nursing documentation were mostly complete, and the quality of handover was mostly good. So it can be concluded that there is a relationship between the completeness of electronic documentation and the quality of handover.